The effect of morphological form variation on adult first language incidental vocabulary acquisition through reading. Issue 1 (8th April 2019) - Reynolds, Barry Lee
Abstract : Purpose: This study aims to investigate the effects of word internal morphological form variation on adult first language (L1) ( n = 20) incidental vocabulary acquisition through reading. Design/methodology/approach: Participants were given a 37, 611-token English novel containing pseudo words, placed throughout the text by the novelist. Two unexpected vocabulary assessments were administered at the completion of the reading task. Findings: Results showed statistically significant effects for morphological form variation, with the readers having incidentally acquired more words whose tokens did not vary in form (i.e. no exposure to inflectional or derivational variants). However, a large effect size was present only for low-frequency words (two-four exposures). Originality/value: Discussion of the results is given regarding the feasibility of enhancing adult L1 college readers' morphological awareness through extensive reading and attention-drawing tasks.